Structural, dielectric and Mossbauer studies of PbFe0.5Sb0.5O3 ceramics with differing degree of compositional ordering. (1st September 2016) - Raevski, I. P.; Pushkarev, A. V.; Raevskaya, S. I.; Olekhnovich, N. M.; Radyush, Yu. V.; Kubrin, S. P.; Chen, H.; Chou, C.-C.; Sarychev, D. A.; Titov, V. V.; Malitskaya, M. A.
ABSTRACT: Ceramic samples of a new perovskite multiferroic PbFe0.5 Sb0.5 O3 (PFS) with a differing degree S of long-range compositional ordering of the Fe 3+ and Sb 5+ cations were fabricated by a variation of the high-pressure-synthesis conditions. The S values estimated from the XRD data varied from 0.93 down to 0.17. The unit cell parameter was found to decrease with increasing S. In line with these results the fraction of the singlet component in the Mössbauer spectra was found to decrease with decreasing S. However, the temperatures and diffusion of dielectric permittivity maxima as well as the temperature of magnetic phase transition determined from Mössbauer data do not change substantially with S. These results imply that PFS remains highly ordered at the nanoscale.